Identification BCL6 and miR-30 family associating with Ibrutinib resistance in activated B-cell-like diffuse large B-cell lymphoma - Li, Jiazheng (Med Oncol, 2021)
Ibrutinib has clear efficacy for activated B-cell-like diffuse large B cell lymphoma (ABC-DLBCL) in previous clinical researches. However, the resistance of Ibrutinib has limited its therapeutic benefit and the potential mechanism remains unclear. This study was aimed to identify potential candidate genes and miRNA targets to overcome Ibrutinib resistance in ABC-DLBCL. First, two expression profiles were downloaded from the GEO database, which used to identify the DEGs related to Ibrutinib resistance in ABC-DLBCL cell lines by GEO2R analysis separately. And the common DEGs were obtained though Venn diagram. Then Gene ontology (GO) and pathway enrichment analysis were conducted by DAVID database. From STRING database, BCL6, IL10, IL2RB, IRF4, CD80, PRDM1and GZMB were determined to be the hub genes by protein–protein interaction (PPI) network. Through miRNA-mRNA targeting network, we found that BCL6, IRF4, CD80, and PRDM1 were common target genes of miR-30 family. The cBioPortal database showed that BCL6 had the highest level of genetic alterations among DLBCL. In addition, another expression profile from GEO database showed that BCL6 was significantly high expression in no responsive patients after Ibrutinib treatment, and the receiver operating characteristic (ROC) curve which was used to evaluate the relationship between BCL6 expression and its effect was 0.67. MTT assay showed that treatment with FX1 (a BCL6 inhibitor) can enhance the sensitivity of Ibrutinib in C481S BTK HBL-1 cells. The results suggested that BCL6 and miR-30 family maybe associate with Ibrutinib resistance in ABC-DLBCL.